Three Cases Developing PTSD After the Explosion and Forensic Psychiatric Evaluation - Özdemir, Miraç; Turan Yurtseven, Nurşen (The Bulletin of Legal Medicine, 2022)
Explosions, rapidly developing; reactions that release heat, gas, and energy. Disorders such as acute stress disorder and post traumatic stress disorder (PTSD) can develop in all kinds of traumatic events, including explosions. PTSD was diagnosed in 3 different blast victims who were sent by the courts at different times, and this diagnosis was evaluated while calculating the disability of the cases. With this presentation, as a different example of trauma; As a result of the evaluations made with the psychiatry clinic in 3 explosion cases; It was aimed to draw attention to the importance of the diagnosed PTSD co-diagnosis in terms of forensic psychiatry and forensic psychotraumatology and to raise awareness.
Keywords: explosion; trauma; post traumatic stress disorder; forensic medicine; forensic psychiatry; forensic psychotraumatology; disability